PENGARUH TINGKAT KESEHATAN PERUSAHAAN ASURANSI TERHADAP PERTUMBUHAN PREMI NETO DAN PROFITABILITAS PERUSAHAAN - Dian Wury Pramestika (Journal of Economics Development Issues, 2019)
This research aimed to indentify and analyze the influence of the health level of insurance company to net premium growth and insurance company’s profitability. There were three variables used in this research: Risk Based Capital (RBC) ratio as the indicator of health level in insurance company, net premium growth, and company’s profitability which is measured by ROE and ROA ratio. Using the secondary data which was collected from annual financial reporting of 10 insurance companies that had been listed in IDX for 5 periods, 2012-2016. The method used to analyze data was by using simple linear regression analysis statistic method. This research found that RBC doesn’t have any influence to net premium growth with significancy 0,430. RBC also has no influence to ROA with significancy 0,51. But this research found that RBC has influence to ROE with significancy 0,031 . The conclusion of the research results indicate that there’s no influence of RBC to net premium growth and ROA but to ROE, in the insurance companies which listed on Indonesia Stock Exchange for 5 periods, 2012-2016.